2020
DOI: 10.1097/rli.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Resonance Imaging Radiomics Signature to Distinguish Benign From Malignant Orbital Lesions

Abstract: Objectives Distinguishing benign from malignant orbital lesions remains challenging both clinically and with imaging, leading to risky biopsies. The objective was to differentiate benign from malignant orbital lesions using radiomics on 3 T magnetic resonance imaging (MRI) examinations. Materials and Methods This institutional review board–approved prospective single-center study enrolled consecutive patients presenting with an orbital lesion undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Third, other texture analysis [ 21 ] such as histogram analysis, run-length matrix analysis are also needed to be involved in the future study. Forth, the two-dimensional delineation of LPM in this study might miss the heterogeneity of the entire muscle compared with the three-dimensional delineation [ 24 ]. Future study needs to design three-dimensional sequence to comprehensively analyze the heterogeneity of LPM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, other texture analysis [ 21 ] such as histogram analysis, run-length matrix analysis are also needed to be involved in the future study. Forth, the two-dimensional delineation of LPM in this study might miss the heterogeneity of the entire muscle compared with the three-dimensional delineation [ 24 ]. Future study needs to design three-dimensional sequence to comprehensively analyze the heterogeneity of LPM.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of studies have confirmed that texture analysis can be used to quantitatively discriminate normal muscle from myopathic muscle [ 20 – 23 ]. What’s more, recent study showed that texture analysis of in-phase image of Dixon sequence might be used to identify the tissue with more heterogeneity [ 24 ]. Therefore, it can be speculated that the texture features extracted from in-phase image are also related to fat fraction of LPM considering the heterogeneity of muscle might be affected by fatty infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the endpoint of interest, various ML classifiers may be used in a radiomics pipeline. Support vector machine (SVM), Bayesian network (BN), multivariate logistic regression (MLR), k-nearest neighbor (kNN), decision trees (DT), random forests (RF), neural network (NNet), and convolutional neural networks (CNN) are among the ML classifiers that are most commonly used in radiomics-based ML pipelines [8][9][10][11][12][13][14][15][16][17][18][19][20] . The feasibility of using radiomics-based ML pipelines to distinguish between benign and malignant bone lesions has been reported in previous studies 1-4, 6, 7 .…”
Section: Radiomics For Bm Detectionmentioning
confidence: 99%
“…In recent years, radiomics-based machine learning (ML) classifiers have shown great potential for use in the early detection of bone metastases (BM) and in assessing response of BM to radiotherapy (RT) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, in order to be clinically acceptable, radiomics models must be trained on large data sets of real-world images.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics enables noninvasive profiling of tissue heterogeneity by extracting quantitative features from radiological images 15,16 . In the field of orbital diseases, several studies have reported its use in improving screening, diagnostic, and predictive performances 17–19 . Duron et al found that MRI‐derived radiomics could assist in differentiating benign from malignant orbital lesions and may outperform expert radiologists 17 .…”
mentioning
confidence: 99%